Queuing System in the Health Sector in Indonesia - Febbi Regita Cahyani; Syamsuddin; Suryadi Hadi; Harnida Wahyuni Adda (Journal of Humanities, Community Service, and Empowerment, 2024)
Queuing systems in the Indonesian healthcare sector play a crucial role in delivering efficient and high-quality services to patients. This study aims to analyze various queuing system models implemented in hospitals and other healthcare facilities, with a primary focus on the FIFO (First-In-First-Out) method. In this system, patients who arrive earlier will be served first. Although the FIFO method has been proven effective in increasing efficiency, various challenges affect the performance of the queuing system, including high patient numbers, limited human resources, and inadequate infrastructure. This study also identifies the potential of technology in optimizing the queuing system, such as information technology-based applications that can expedite the registration process and reduce patient waiting times. During the COVID-19 pandemic, the health sector in Indonesia has been increasingly encouraged to adopt digital technology in queue management, which can improve the quality of health services. This technology can enhance the flow of information to patients and aid in setting queue priorities, particularly for vulnerable groups such as the elderly and pregnant women. Additionally, government policies that support digitalization in the healthcare sector also play a crucial role in overcoming various existing obstacles. By employing a holistic approach that incorporates infrastructure, technology, and human resources, it is anticipated that the queue system in the Indonesian healthcare sector can be significantly improved, offering faster and more efficient services and enhancing patient satisfaction.